2017
DOI: 10.21037/jtd.2017.09.112
|View full text |Cite
|
Sign up to set email alerts
|

Management of occult malignant pleural disease firstly detected at thoracotomy for non-small cell lung cancer patients

Abstract: Background: The current study was to investigate the risk factors of occult malignant pleural disease (MPD) detected at thoracotomy and the outcomes of surgical intervention for these non-small cell lung cancer (NSCLC) patients with or without MPD. Conclusions:We summarized that a new prediction model including 5-risk factors of age, carcinoembryonic antigen (CEA), N stage, adenocarcinoma and pleural invasion was provided to diagnose MPD for the NSCLC patients and primary lesion resection greatly contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…According to the previous studies, the OS, 3- and 5-year survival rate of NSCLC patients with PD were 15–52 months, 25.2–69.2% and 16.0–42.7%, respectively ( 1 , 7 9 , 11 , 17 , 21 , 22 , 24 ). Furthermore, the OS, 3- and 5-year survival rate were 20–64 months, 45.8–82.9%, and 31.4–42.7% for patients with primary tumor resection, while 7–35 months, 11.8–41.7%, and 0–19.5% for patients with biopsy alone.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…According to the previous studies, the OS, 3- and 5-year survival rate of NSCLC patients with PD were 15–52 months, 25.2–69.2% and 16.0–42.7%, respectively ( 1 , 7 9 , 11 , 17 , 21 , 22 , 24 ). Furthermore, the OS, 3- and 5-year survival rate were 20–64 months, 45.8–82.9%, and 31.4–42.7% for patients with primary tumor resection, while 7–35 months, 11.8–41.7%, and 0–19.5% for patients with biopsy alone.…”
Section: Discussionmentioning
confidence: 88%
“…However, the time span of this study was relatively short and recent (6 years from 2010) compared with other studies ( 1 , 16 , 17 , 19 , 24 ), and no patient was lack of pathological confirmation for malignant PD, unlike other studies ( 16 , 19 ). Besides, the sample size of this study was relatively larger than previous studies, as well as longer follow-up time ( 1 , 7 , 12 , 14 , 15 , 22 ). Additionally, several studies reported that N0 stage was the independent prognostic factor for survival, which, however, has potential bias, given that many patients did not have completely pathological N status ( 1 , 26 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The opposite conclusions of the two similar studies might due to the differences in adjuvant treatment and surgical methods. Then, in the last two decades, several single-center retrospective studies with sample sizes ranging from 25 to 138 also reported outcomes of unexpected M1a patients undergoing PTR, with MSTs ranging from 15-64 months and 3-year OSs ranging from 34.2% to 82.9%, 5-year OSs ranging from 16.3-42.7%, respectively (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Most studies supported PTR as a significant prognostic factor for better survival for patients intraoperatively diagnosed as M1a.…”
Section: For Cm0 Patientsmentioning
confidence: 99%
“…In the last 10 years, targeted therapy, such as TKIs for EGFR or anaplastic lymphoma kinase (ALK), significantly improved the survival of driver-oncogene positive stage IV NSCLC patients (35). According to previous literatures, adenocarcinoma is the most common histology subtype in pM1a patients, with a prevalence of 64% to 90.9% (15,(17)(18)(19)(20)(21)(22)(23)(24)(25)27,30,31,33,34). Thus, pM1a patients are likely to benefit from targeted therapy.…”
Section: Surgery For Patients With Different Genetic Mutationsmentioning
confidence: 99%